Autoimmunity-Associated PTPN22 Polymorphisms in Latent Autoimmune Diabetes of the Adult Differ from Those of Type 1 Diabetes Patients - Heneberg, Petr; Kocková, Lucie; Čecháková, Marie; Daňková, Pavlína; Černá, Marie (International archives of allergy and immunology, 2018)
BACKGROUND: A portion of adults with humoral immune changes have clinical diabetes that is initially not insulin-requiring (latent autoimmune diabetes of the adult, LADA). One of the genes strongly associated with autoimmune diabetes is PTPN22. We hypothesized that the manifestation and clinical features of LADA are linked to functional variants of PTPN22. METHODS: We genotyped allelic frequencies of 1 protective and 3 risk-associated PTPN22 variants in 156 Czech LADA patients, 194 type 2 diabetes mellitus patients with LADA-like progression to insulinotherapy and 324 type 1 diabetes mellitus patients, and subsequently examined the associations of PTPN22 variants with the expression of autoantibodies and other clinical features of LADA. RESULTS: We challenged the paradigm that stated that the PTPN22 c.1858T allele serves as a risk allele for LADA, although we confirmed its risk status in the geographically matched T1DM cohort. In contrast, the frequencies of other PTPN22 alleles (c.-1123C, c.788A and c.1970-852C) differed significantly from the healthy controls. We confirmed gender-related differences in the frequency of some PTPN22 polymorphisms (but not c.1858C>T) in LADA. The particular PTPN22 alleles and genotypes were associated with specific clinical features of the examined patients (autoantibodies, HbA1c and age at diagnosis of diabetes). CONCLUSIONS: The variability in PTPN22 haplotypes suggests that the genetic signature of LADA is independent and should not be considered a hybrid form of T1DM and T2DM. Further studies should elucidate the associations with clinical characteristics of the LADA patients and focus on the newly emerging types of diabetes with the disease onset in early to mid-adulthood.
Keywords: Latent autoimmune diabetes of the adult; dospělí; latentní autoimunitní diabetes dospělých; diferenciální diagnóza; odds ratio; Genotype; Female; Phenotype; Lymphoid-specific tyrosine phosphatase; biologické markery; Biomarkers; Adult; ženské pohlaví; jednonukleotidový polymorfismus; Diabetes Mellitus, Type 2; Gene Frequency; lidé; Polymorphism, Single Nucleotide; genotyp; Protein Tyrosine Phosphatase, Non-Receptor Type 22; PTPN22; diabetes mellitus 2. typu; genetická predispozice k nemoci; Genetic Predisposition to Disease; frekvence genu; Diagnosis, Differential; Humans; Diabetes Mellitus, Type 1; Latent Autoimmune Diabetes in Adults; genetické asociační studie; Male; Aged; Autoantibodies; polymorfismus genetický; Genetic Association Studies; alely; Adult-onset autoimmune diabetes; ICA512; Alleles; PTPRN; lidé středního věku; senioři; mužské pohlaví; fenotyp; tyrosinfosfatasa nereceptorového typu 22; Polymorphism, Genetic; Middle Aged; diabetes mellitus 1. typu; Odds Ratio; autoprotilátky